Contrasting changes of snow cover between different regions of the Tibetan Plateau during the latest 21 years - Gao, Yang; Dong, Huaiwei; Dai, Yufeng; Mou, Naixia; Wei, Wenfan (Frontiers in Earth Science, 2023)
The spatial and temporal resolution of snow remote sensing data has been increasing, but the unique snow characteristics such as thin snow depth and high frequency of change on the Tibetan Plateau have limited their applicability in this region. In this study, five commonly used snow remote sensing data were evaluated based on snow observations at 139 stations during the latest 20 years, and the advantages of each data were integrated to develop a multi-source data fusion snow cover dataset for the Tibetan Plateau. Based on this data, we conducted snow zonation and comparative snow variability analysis on the Tibetan Plateau. Results indicated that the snow cover days on the Tibetan Plateau are not only influenced by the longest snow cover duration (SCD), but also controlled by the short-term snow cycles. More than 70% of the annual snow cover days comes from short-term snow cycles, except the Amu Darya and Indus. From 2000 to 2021, 23.0% of the Plateau has experienced a significant decrease in snow cover days (mainly in the southeast) and 4.9% has experienced a significant increase (mainly in the northwest). As the altitude increases, the area and magnitude of decreased and increased snow cover increases, and at high altitude the areas with increased snow are greater than that with decreased. The significant reduction in the snow cover days over large areas of the plateau stems from the superimposed effect of the simultaneous reductions in the longest SCD and the short-term snow cycles, but the reduction in the Amu Darya and Indus comes mainly from the reduction in the short-term snow cycle. The significant increase in the snow cover days in Amu Darya, Indus, Tarim and Hexi mainly comes from the increase in the longest SCD, while that in Yellow River and Qaidam mainly comes from the increase in the short-term snow cycles. This contrasting change in the snowpack on the Tibetan Plateau, which decreases in the southeast and increases in the northwest, with a large decrease at lower elevations and an increase at higher elevations, will bring new challenges to water resources management in the region.